Combined heat and power system based on a proton conducting SOFC and a supercritical CO2 Brayton cycle triggered by biomass gasification. (26th January 2022) - Cao, Yan; Dhahad, Hayder A.; Rajhi, Ali A.; Alamri, Sagr; Anqi, Ali E.; El-Shafay, A.S.
Abstract: An integrated combined heat and power system was developed by combination of a proton conducting solid oxide fuel cell and a supercritical carbon dioxide Brayton cycle triggered by air-gasification of peach stone. Equivalence ratio, fuel cell temperature, fuel utilization factor and pressure ratio were considered as parameters with respect to power and heat productions as response variables. Analysis of variance showed that fuel utilization factor and fuel cell temperature with shares of 76.6% and 11.5% contribute the most on the power production while the most important factors on heat production are fuel utilization factor and equivalence ratio with shares of 54.1% and 44.8%, respectively. Power production is improved by increasing fuel cell temperature, decreasing equivalence ratio and decreasing fuel utilization factor. Regression models for predicting power (with R 2 of 98.47%) and heat (with R 2 of 91.77%) were proffered using analysis of variance with errors smaller than 1%. Multi-objective optimization results revealed that equivalence ratio of 4, fuel cell temperature of 680 °C, fuel utilization factor of 0.82 and pressure ratio of 5.11 were optimum conditions to achieve the maximum power (138 kW) and heat (195 kW). Graphical abstract: Image 1 Highlights: Proton conducting SOFC was integrated with supercritical CO2 Brayton cycle. This integrated system was driven by peach stone gasification. A combined power and heat generation system was developed. Power and heat generations were maximized using response surface methodology. Effective parameters were identified using analysis of variance.